(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article explores the cultural distinctions between Uzbekistan and other global cultures and analyzes how these differences influence the educational upbringing of children. Emphasizing the role of culture in shaping values, identity, and learning styles, the paper underscores the importance of integrating cultural sensitivity into educational practices. Through comparative analysis and real-world observations, the study highlights both the strengths and challenges posed by cultural diversity in modern education and proposes strategies for creating inclusive, culturally aware learning environments.